The Influence of Social Media Activity Dimensions on Consumer Emotional Attachment: Pengaruh Dimensi Social Media Activity Terhadap Emotional Attachment Konsumen - Leni, Puspa; Mulya, Jumiatul (International Journal of Management and Business (IJMB), 2024)
This study aims to determine how the dimensions of social media activity influence, namely Social media Interactivity, social media benefits and social media rewards on the Emotional attachment of consumers of Kedai Kopi Janji Jiwa. This study uses a quantitative research method with an associative design. The population in this study were people in Padang City. The number of samples in this study was 200 respondents. The data analysis technique used was multiple linear regression analysis using hypothesis testing, namely the t-test and F-test. The results of this study indicate that partially Social media Interactivity, and social media rewards have a positive and significant effect, while social media benefits have a positive but insignificant effect on online buying interest in the fashion category on Lazada. Based on the F test, product quality and price simultaneously have a positive and significant effect on the Emotional attachment of consumers of Kedai Kopi Janji Jiwa. The Adjusted R-Square value is 0.396 or 39.6% while the remaining 60.1% is influenced by other variables not examined in this study, such as brand image. Thus, it can be concluded that if you want to increase the emotional attachment of consumers, the manager of the Janji Jiwa Coffee shop in Padang City can increase activities on social media, especially social media interactivity and social media rewards.